Chemometrics based GC-MS aroma profiling for revealing freshness, origin and roasting indices in saffron spice and its adulteration. (30th November 2020) - Farag, Mohamed A.; Hegazi, Nesrine; Dokhalahy, Eric; Khattab, Amira R.
Highlights: GC-MS volatiles profiling of saffron and its adulterants. The first complete map for saffron aroma via SPME is presented. Modeling revealed for saffron freshness and ageing indices. Methodology can be utilized as quality control tool for saffron raw material. Abstract: Saffron, stigmas of Crocus sativus, is one of the most precious spices used as food colorant and flavoring agent. Due to its scarce source and high cost, it is liable to fraudulent admixture with allied plants "safflower and calendula". In this study, gas chromatography-mass spectrometry (GC-MS) was employed to determine authenticity, adulterants detection, and to assess the roasting impact on its aroma. A total of 93 volatiles were identified belonging to different classes viz. aldehydes, alcohols, ketones, aliphatic hydrocarbons, aromatics, mono-and sesquiterpenes, oxides/ethers and pyrans/furans. Principle component analysis (PCA) identified safranal and 2-caren-10-al as discriminatory volatile markers of saffron from its allied flowers, later found enriched in estragole, β -caryophyllene and eugenol. PCA model also revealed markers for freshly dried versus long-stored saffron, with ketoisophorone as freshness marker versus safranal as an ageing indicator. Safranal was further identified as a marker to distinguish saffron from safflower, whereas calendula aroma was predominated by monoterpene hydrocarbons.